Harnessing genome editing for developing climate-resilient crops - Mann, Anita; Sanwal, S. K.; Kumar, Ashwani; Prakash, Nitish Ranjan; Dahiya, Avni; Kumar, Arvind; Kumar, Arvind; Yadav, R. K. (Indian Farming, 2025)
Climate change poses a serious threat to world agriculture and food security due to the increasing frequency of drought, salinity, heat, and other biotic or abiotic stresses. As a result, the development of climate-resilient crops has become an urgent priority to maintain productivity in vulnerable ecosystems. Recent technologies of genome editing using CRISPR/Cas are precise, accurate and efficient tools for accelerating crop improvement. With genome editing, stress-responsive genes, regulatory components, and metabolic pathways can be specifically altered without the hassles of linkage drag or drawn-out breeding cycles. Recent advancements have successfully edited genes linked to osmotic adjustment, antioxidant regulation, ion homeostasis, disease resistance and stress signalling pathways in cereals, legumes, and oilseeds, leading to improved crop plants. In addition to resilience against abiotic stresses, editing for characteristics such as nitrogen-use efficiency, photosynthetic performance, and yield stability in variable climates presents a promising pathway for sustainable agriculture. The integration of genome editing with genomic selection, speed breeding, and high-throughput phenotyping can further expedite the creation of resilient varieties. This article emphasizes significant breakthroughs, potential gene targets, and translational strategies for implementing genome editing in crop breeding initiatives. Leveraging these innovations can greatly enhance global food and nutritional security in the context of climate change.